Market response to land auction events: a transaction volume approach. Issue 1 (2nd March 2015) - Chiu, Shuk Man; Chau, Kwong Wing; Yau, Yung
Abstract : Purpose: – The purpose of this paper is to investigate the response of transaction volume in Hong Kong's housing market to public land auctions. Design/methodology/approach: – An event study approach with the use of regression analyses was adopted for the empirical study. Findings: – Fewer pre-event transactions in the secondary housing spot market come with greater dispersion in the pre-event forecasts of land auction outcomes. Unexpected auction outcomes were also found to minify the post-event transaction volume in the secondary housing spot market, with negative unexpected outcomes exerting a stronger downward force. Research limitations/implications: – These findings are contrary to the empirical evidence commonly found in most financial literature on stock transaction volume around corporate earnings announcements with an assumption of negligible transaction costs. Imperfect market structure, differences in sellers' and buyers' characteristics and short-sale restriction may explain the disparity. Practical implications: – Price in the secondary housing market is more sensitive to negative unexpected land auction outcomes. The analysis results of the current study attest that the impact exerted by the negative unexpected auction outcomes on transaction volume in the housing spot market is stronger than that of positive unexpected auction outcomes. Originality/value: – Unlike price and return, transaction volume has not received substantial academic attention in property research. In particular, within the existing small body of transaction volume research, the impact of information events on trading activities has been largely ignored.